Market integration and forecast performances of stock market and macroeconomic volatilities in global financial crises - Tokmakçıoğlu, Kaya (Fen Bilimleri Enstitüsü, 2012)
This thesis focuses on the analysis of the integration of 17 important stock markets and forecast performances of stock market and macroeconomic volatility for the period of last global, financial crisis. The results of the first section generally support the findings of previous literature on market integration. In order to examine the linkages of 17 national stock markets, cointegration, impulse response and variance decomposition analysis are performed, before and during the period of the global financial crisis of 2007. According to the results, it has been found that the cointegrational relationship had improved globally during the period of global crisis. This work also has explored the effects of financial volatility during the last global crisis. According to the literature, volatility in financial markets increases severely during the crises. This thesis, which underlines the importance of stock market volatility during financial crises, introduces another important tool to assess the volatility clustering behavior, namely macroeconomic volatility. Thus, the key finding of this work is that the forecast performance of stock market volatility surpasses the forecast performance of macroeconomic volatility.

Bu tez 17 hisse senedi piyasasının bütünleşmesine ve bu ekonomilerin hisse senedi piyasası oynaklığı ile makroekonomik oynaklıklarının son küresel finansal kriz süresince çözümlenmesine odaklanmıştır. İlk bölümün sonuçları genel olarak piyasa bütünleşmesi hakkındaki literatürü destekler niteliktedir. 17 ulusal hisse senedi piyasası arasındaki bağlantıyı incelemek için 2007 küresel krizi öncesinde ve kriz süresi boyunca sırasıyla eşbütünleşme, dürtü yanıtı ve varyans ayrıştırma analizleri gerçekleştirilmiştir. Sonuçlara göre kriz dönemi boyunca küresel olarak eşbütünleşme ilişkisi artmıştır. Diğer taraftan çalışmada son küresel krizde finansal oynaklığın etkileri de incelenmiştir. Literatüre göre finansal piyasalardaki oynaklık kriz dönemlerinde ciddi bir biçimde artmaktadır. Finansal kriz dönemlerinde hisse senedi piyasası oynaklığının önemini tekrar vurgulayan bu tez, makroekonomik oynaklığı da göz önünde bulundurarak oynaklık kümelenmesi davranışını çözümlemeye yönelik yeni bir adım atmıştır. Sonuç olarak bu tezin önemli bulgularından biri, hisse senedi piyasası oynaklık tahmin performansının makroekonomik oynaklık tahmin performansından üstün olduğudur.
Küresel finansal krizlerde piyasa bütünleşmesi ve hisse senedi piyasası ile makroekonomik oynaklıkların tahmin performansları
Keywords: Financial movements, Financial crisis , GARCH model ,Volatility,Market value; Finansal hareketler ,Finansal kriz ,GARCH model , Oynaklık , Piyasa değeri